Novel Multiwavelength Microscopic Scanner for Mouse Imaging - Alencar, Herlen (Neoplasia Press, Inc., 2005)
Real-time in vivo imaging of molecular targets at (sub)cellular resolution is essential in better understanding complex biology. Confocal microscopy and multiphoton microscopy have been used in the past to achieve this goal, but their true capabilities have often been limited by bulky optics and difficult experimental set-ups requiring exteriorized organs. We describe here the development and validation of a unique near-infrared laser scanning microscope system that uses novel optics with a millimeter footprint. Optimized for use in the far red and near-infrared ranges, the system allows an imaging depth that extends up to 500 μm from a 1.3-mm-diameter stick objective, which is up to 2 cm in length. We show exceptionally high spatial, temporal, and multiwavelength resolutions of the system and show that it can be applied to virtually any internal organ through a keyhole surgical access. We demonstrate that, when combined with novel far red imaging probes, it is possible to image the cellular details of many organs and disease processes. The new optics, coupled with the use of near-infrared probes, should prove immensely valuable for in vivo cancer imaging.